2019
DOI: 10.1653/024.102.0306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plastic Packaging for Prevention of Damage to Wheat by Trogoderma granarium (Coleoptera: Dermestidae), and Suitability of Phosphine Fumigation

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Foodstuff packaging derived from plastics like polypropylene with a thickness of 0.04 mm was found to be resistant to insect penetrations or invasions of a major stored grain borer, Rhyzopertha dominica ( Hassan et al, 2016 ). Previous research done by the study researchers evaluating the susceptibility of flexible plastic foodstuff packaging found that major stored grain insects were able to tear plastic packaging and consume or remove some of the food inside, leading to weight loss in the packaged foodstuffs ( Qasim et al, 2013 ; Hassan et al, 2014 ; Hassan et al, 2016 ; Yar et al, 2017 ; Akram et al, 2018 ; Hussain et al, 2019 ; Waheed et al, 2022 ). However, little or no research is currently available on the susceptibility of commonly-used flexible plastic foodstuff packaging against household ants.…”
Section: Introductionmentioning
confidence: 99%
“…Foodstuff packaging derived from plastics like polypropylene with a thickness of 0.04 mm was found to be resistant to insect penetrations or invasions of a major stored grain borer, Rhyzopertha dominica ( Hassan et al, 2016 ). Previous research done by the study researchers evaluating the susceptibility of flexible plastic foodstuff packaging found that major stored grain insects were able to tear plastic packaging and consume or remove some of the food inside, leading to weight loss in the packaged foodstuffs ( Qasim et al, 2013 ; Hassan et al, 2014 ; Hassan et al, 2016 ; Yar et al, 2017 ; Akram et al, 2018 ; Hussain et al, 2019 ; Waheed et al, 2022 ). However, little or no research is currently available on the susceptibility of commonly-used flexible plastic foodstuff packaging against household ants.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier research for management of important storage pests in packaged foodstuffs included evaluation of some frequently used plastic packing for their resistance to external insect infestation in these bags and their efficacy for the vital fumigant (phosphine) gas permeation if infestation was already present in foodstuffs; this included evaluation of polyethylene, polypropylene, and polyvinylchloride packaging against different insect pests, namely Tribolium castaneum , T. granarium , and R. dominica [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dermestidae (skin, larder, hide, leather, carpet, and khapra beetles) are among a few coleopterous families widely known to the public due to their occasional presence in homes where they pose a hygiene problem, damage wool fabrics and furs, and infest stored products (Battisti et al, 2011;Hussain et al, 2019). Some species are well known to curators of natural history collections, forensic entomologists, industrial storage space keepers and disinsection specialists (Anton et al, 2011;Querner, 2015).…”
Section: Introductionmentioning
confidence: 99%